Impact of COVID-19 on poverty and living standards in Ghana: A micro-perspective - Chei Bukari; Gloria Essilfie; Millicent Abigail Aning-Agyei; Isaac Christopher Otoo; Christian Kyeremeh; Anthony Akwesi Owusu; Kofi Fosu Amuquandoh; Kpanja Ibrahim Bukari (Cogent Economics & Finance, 2021)
The novel Coronavirus disease 2019 (COVID-19), which has become a global epidemic, hit Ghana on 12 March 2020 and, in less than a week, increased by over 300% with two deaths. As of 11 August 2020, Ghana had recorded over 41,000 cases with over 215 deaths. This study seeks to provide a micro-level evidence on how COVID-19 is posing a threat to some of the Sustainable Development Goals, particularly poverty in Ghana. Specifically, the study examined the effect of COVID-19 on poverty and living standards of Ghanaian households. The study further analysed which class of persons within the income distributions has been mostly hit by the pandemic. Data on 3,905 households were obtained via concurrent online survey and telephone interviews. Multiple analytical approaches were employed―Ordinary least squares, probit model and simultaneous quantile regressions. Results showed that COVID-19 had significantly increased the poverty levels of households while deteriorating living standards. The study also discovered that gender and locational heterogeneities exist regarding the impact of COVID-19 with females and rural dwellers mostly disadvantaged. However, simultaneous quantile regression result shows that in terms of overall household consumption, those in the middle and upper classes are profoundly affected compared to those in the lowest class. A key policy implication from this study is that Ghana needs to broaden its social protection programmes to assist both the new poor and existing poor.
Keywords: I31; I32; 330; COVID-19; Ghana; living standards; pandemic; poverty